KONVERGENSI INTERNATIONAL FINANCIAL REPORTING STANDARDS (IFRS) DAN MANAJEMEN LABA DI INDONESIA - Lestari, Yona Octiani (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2011)
The existence of convergence of accounting standards to IFRS create a new paradigm in the accounting world. This requires the convergence of IFRS accounting standards that have been used to adopt new accounting standards with IFRS. The convergency accounting standards to IFRS increase a variety of influences, in accordance with IFRS characteristics such as : principle based, the use of fair value and more disclosure. Principle Based Standards require more judgment in its application, while the used of fair value items make the financial statements are presented with the actual values, more disclosure would reduce the level of information asymmetry. Convergence of IFRS is expected increasing financial reporting quality, such as, increased camparability and transparency of financial statements. Thus, with the convergence to IFRS expected reduce earnings management opportunities.